2023
DOI: 10.3389/fcimb.2023.1053968
|View full text |Cite
|
Sign up to set email alerts
|

Deciphering the virulence factors, regulation, and immune response to Acinetobacter baumannii infection

Abstract: Deciphering the virulence factors, regulation, and immune response to Acinetobacter baumannii infectionAcinetobacter baumannii is a gram-negative multidrug-resistant nosocomial pathogen and a major cause of hospital acquired infetions. Carbapenem resistant A. baumannii has been categorised as a Priority1 critial pathogen by the World Health Organisation. A. baumannii is responsible for infections in hospital settings, clinical sectors, ventilator-associated pneumonia, and bloodstream infections with a mortalit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 232 publications
(237 reference statements)
0
19
0
Order By: Relevance
“…Through a wide range of pan-genomic studies, it has been recognized that A. baumannii is an open pan-genomic bacterial pathogen; hence, A. baumannii encompasses a variety of virulence factors with different functions and activities. Because of the importance of these virulence factors, Table 1 shows a complete package of the identified virulence factors together with the related genes [ 3 , 68 , 69 ].…”
Section: Virulencementioning
confidence: 99%
See 1 more Smart Citation
“…Through a wide range of pan-genomic studies, it has been recognized that A. baumannii is an open pan-genomic bacterial pathogen; hence, A. baumannii encompasses a variety of virulence factors with different functions and activities. Because of the importance of these virulence factors, Table 1 shows a complete package of the identified virulence factors together with the related genes [ 3 , 68 , 69 ].…”
Section: Virulencementioning
confidence: 99%
“…CPS is known as the main virulence factor arming A. baumannii stains. This structure acts as a superficial multifunctional virulence factor that pathogenic bacteria like A. baumannii use to survive in unfavorable environmental conditions, such as the presence of antimicrobials, human host cell immune defense mechanisms and prolonged desiccation ( Table 2 ) [ 68 , 71 , 72 ]. The omission of CPS expression in CPS-producing A. baumannii strains may significantly affect bacterial virulency and pathogenesis.…”
Section: Virulencementioning
confidence: 99%
“…Of note, A. baumannii benefits from virulence factors such as outer membrane proteins (OMPs), metal ion acquisition systems, lipopolysaccahrides (LPS), efflux pumps, empowering it to survive harsh environments (e.g. host immune system, hospital environments) and resist antibiotics (15)(16)(17)(18)(19)(20)(21)(22)(23)(24). Several studies have demonstrated that mAbs targeting these virulence factors could provide protection against infections caused by multidrug resistant (MDR) or extensively drug resistant (XDR) A. baumannii in animal models (15,(25)(26)(27)(28).…”
Section: Introductionmentioning
confidence: 99%
“…The virulence of A. baumannii is multifactorial, determined by the combination of multiple factors such as efflux pumps (adeRS), quorum sensing (aba), siderophores (bar, bas, bau), biofilm (bap), secretion systems (pil, TXSS), and one of the most important factors, the capsule [10].…”
Section: Introductionmentioning
confidence: 99%